Legal Protection for Victims of Wrongful Arrest and Persecution by Investigators (Case Study of Badia Raja Situmorang) - Arifin, Wandi (Indonesia Media Law Review, 2023)
Law enforcement by the police often raises public attention, one of which is the various cases of wrongful arrest by the police. In fact, many related studies have shown that cases of wrongful arrests have the potential to violate various human rights. This study aims to analyze the legal protection for victims of wrongful arrests in the Badia Raja Situmorang case. This study uses a normative juridical approach, with the support of victimization criminology studies. This study finds and confirms that in relation to cases of wrongful arrest, various legal rules can be used, starting from the Human Rights Law, the Child Protection Law, the Criminal Procedure Law, to the Witness and Victim Protection Act. At the investigation stage in the Badia case, the victim experienced physical violence, resulting in a violation of the investigation procedures carried out.